2022
DOI: 10.1002/ece3.8694
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance alters relationships between soil carbon pools and aboveground vegetation attributes in an anthropogenic peatland in Patagonia

Abstract: Anthropogenic‐based disturbances may alter peatland soil–plant causal associations and their ability to sequester carbon. Likewise, it is unclear how the vegetation attributes are linked with different soil C decomposition‐based pools (i.e., live moss, debris, and poorly‐ to highly‐decomposed peat) under grassing and harvesting conditions. Therefore, we aimed to assess the relationships between aboveground vegetation attributes and belowground C pools in a Northern Patagonian peatland of Sphagnum magellanicum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 74 publications
0
0
0
Order By: Relevance
“…Analyses were conducted independently for the forest and peatland sites. We used a partial least-squares path modelling (PLS-PM or PLS-SEM; Tenenhaus et al, 2005), a non-parametric compositebased SEM that has shown potential in analysing large sets of ecological and environmental data (Ferner et al, 2018;Lopatin et al, 2015Lopatin et al, , 2019Lopatin et al, , 2022Lopatin, 2023). PLS-PM uses ordinary least-squares regression for estimating the path coefficients and has been found to be flexible to model interactions using a reflective or a formative conceptualisation, which dramatically alters the method of the measurement approximation (e.g.…”
Section: Assessing the Environmental Drivers Of The Fluxesmentioning
confidence: 99%
“…Analyses were conducted independently for the forest and peatland sites. We used a partial least-squares path modelling (PLS-PM or PLS-SEM; Tenenhaus et al, 2005), a non-parametric compositebased SEM that has shown potential in analysing large sets of ecological and environmental data (Ferner et al, 2018;Lopatin et al, 2015Lopatin et al, , 2019Lopatin et al, , 2022Lopatin, 2023). PLS-PM uses ordinary least-squares regression for estimating the path coefficients and has been found to be flexible to model interactions using a reflective or a formative conceptualisation, which dramatically alters the method of the measurement approximation (e.g.…”
Section: Assessing the Environmental Drivers Of The Fluxesmentioning
confidence: 99%
“…Analyses were conducted independently for the forest and peatland sites. We used a partial least-squares path modelling (PLS-PM or PLS-SEM; Tenenhaus et al, 2005), a non-parametric compositebased SEM that has shown potential in analysing large sets of ecological and environmental data (Ferner et al, 2018;Lopatin et al, 2015Lopatin et al, , 2019Lopatin et al, , 2022Lopatin, 2023). PLS-PM uses ordinary least-squares regression for estimating the path coefficients and has been found to be flexible to model interactions using a reflective or a formative conceptualisation, which dramatically alters the method of the measurement approximation (e.g.…”
Section: Assessing the Environmental Drivers Of The Fluxesmentioning
confidence: 99%